Isolated nano-tendril bundles on tungsten surfaces exposed to radiofrequency helium plasma. (August 2017) - Woller, Kevin B.; Whyte, Dennis G.; Wright, Graham M.
Highlights: Modulation of incident ion energy at a frequency of 13.56 MHz affects the resulting surface morphology of tungsten during exposure to helium plasma. Nano-tendril bundles and unsupported whiskers are observed with <10% coverage of the surface. Isolated structures provide critical evidence of alternative surface modification over W fuzz in RF environments. Abstract: The DIONISOS experiment is used to study the impact of RF helium (He) plasma on the surface morphology of tungsten (W) at a frequency of 13.56 MHz. Helium ion energy distributions with a span of 70–75 eV, while still below the sputtering threshold result in nano-tendril bundles (NTBs) and free-standing W whiskers on surfaces at 1020 K. The NTBs are distributed intragranularly with coverage of less than 10% while reaching up to 30 µm normal to the surface for He ion fluence of 7.6 × 10 25  m −2 and flux density of 10 22  m −2  s −1 . Analysis of the NTB interior and sub-surface structure is provided through focused ion beam cross section.